Scientific Capital as a Driver of Researchers’ Social Mobility - Natalia Shmatko (Foresight and STI Governance)
Changes in the structure and priorities of research funding and of educational activities accompany changes in the labour market for scientists, including newly induced mobility both on a national and an international level. The paper aims to operationalize the concept of social mobility, separating it from directly observable relocations. Second, it builds a structural model explaining the results of measured mobility.